Biomarkers for central nervous system injury in cerebrospinal fluid are elevated in COVID‐19 and associated with neurological symptoms and disease severity. (19th January 2021) - Virhammar, Johan; Nääs, Anja; Fällmar, David; Cunningham, Janet L.; Klang, Andrea; Ashton, Nicholas J.; Jackmann, Sven; Westman, Gabriel; Frithiof, Robert; Blennow, Kaj; Zetterberg, Henrik; Kumlien, Eva; et al.
Abstract: Background and purpose: Neurological symptoms have been frequently reported in hospitalized patients with coronavirus disease 2019 (COVID‐19), and biomarkers of central nervous system (CNS) injury are reported to be increased in plasma but not extensively studied in cerebrospinal fluid (CSF). This study examined CSF for biomarkers of CNS injury and other pathology in relation to neurological symptoms and disease severity in patients with neurological manifestations of COVID‐19. Methods: Nineteen patients with neurological symptoms and mild to critical COVID‐19 were prospectively included. Extensive analysis of CSF, including measurement of biomarkers of CNS injury (neurofilament light chain [NfL] protein, glial fibrillary acidic protein [GFAp], and total tau), was performed and compared to neurological features and disease severity. Results: Neurological symptoms included altered mental status (42%), headache (42%), and central (21%) and peripheral weakness (32%). Two patients demonstrated minor pleocytosis, and four patients had increased immunoglobulin G levels in CSF. Neuronal autoantibody testing using commercial tests was negative in all patients. Increased CSF levels of NfL protein, total tau, and GFAp were seen in 63%, 37%, and 16% of patients, respectively. Increased NfL protein correlated with disease severity, time in intensive care, and level of consciousness. NfL protein in CSF was higher in patients with central neurological symptoms. Conclusions: Although limited by the small sample size, our data suggest that levels of NfL protein, GFAp, and total tau in CSF are commonly elevated in patients with COVID‐19 with neurological symptoms. This is in contrast to the standard CSF workup where pathological findings are scarce. NfL protein, in particular, is associated with central neurological symptoms and disease severity. Abstract : Neurofilament light chain (NfL) protein in cerebrospinal fluid is increased in patients with neurological symptoms and COVID‐19. NfL protein correlated with disease severity and was higher in patients with central neurological symptoms.